2020
DOI: 10.1001/jamaneurol.2020.0311
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sleep-Disordered Breathing With Alzheimer Disease Biomarkers in Community-Dwelling Older Adults

Abstract:  Question: Which brain changes are associated with sleep-disordered breathing (SDB) in aging?  Findings: In this cross-sectional study of 127 cognitively unimpaired communitydwelling older individuals, the presence of SDB was associated with greater amyloid burden, gray matter volume, metabolism, and perfusion in the posterior cingulate cortex and precuneus. There was no association with cognitive performance, selfreported cognitive or sleep difficulties, nor excessive daytime sleepiness.  Meaning: SDB-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
70
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(87 citation statements)
references
References 59 publications
(127 reference statements)
5
70
2
1
Order By: Relevance
“…Obstructive sleep apnea (OSA) increases Alzheimer's disease (AD) risk [1][2][3][4][5][6] and at cross-section, is associated with AD biomarkers, including the presence of significant brain amyloid beta (Aβ) and tau burden, measured either by cerebrospinal (CSF) Aβ42 or amyloid positron emission tomography (PET), and CSF levels of tau (ie, total or hyperphosphorylated) or tau-PET, in both cognitive normal (CN) and mild cognitive impaired (MCI) participants. [7][8][9][10][11][12][13][14] Recently, our group found that this cross-sectional association was not found in participants with Pittsburgh compound B (PiB)-negative scans, 15 suggesting that the presence or absence of amyloid burden might act as a moderator in these relationships. A previous cross-sectional study suggested a similar phenomenon, with associations seen between increased amyloid deposition and higher apnea hypopnea index indices in MCI patients but not among CN controls.…”
Section: Introductionmentioning
confidence: 99%
“…Obstructive sleep apnea (OSA) increases Alzheimer's disease (AD) risk [1][2][3][4][5][6] and at cross-section, is associated with AD biomarkers, including the presence of significant brain amyloid beta (Aβ) and tau burden, measured either by cerebrospinal (CSF) Aβ42 or amyloid positron emission tomography (PET), and CSF levels of tau (ie, total or hyperphosphorylated) or tau-PET, in both cognitive normal (CN) and mild cognitive impaired (MCI) participants. [7][8][9][10][11][12][13][14] Recently, our group found that this cross-sectional association was not found in participants with Pittsburgh compound B (PiB)-negative scans, 15 suggesting that the presence or absence of amyloid burden might act as a moderator in these relationships. A previous cross-sectional study suggested a similar phenomenon, with associations seen between increased amyloid deposition and higher apnea hypopnea index indices in MCI patients but not among CN controls.…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, oral devices or, in extreme cases, surgical procedures are available [2]. A growing body of evidence has shown the impact of OSA on reduced cognition [5][6][7][8][9], brain morphology [3,[10][11][12][13], and neurodegenerative pathophysiology [11,[14][15][16][17][18]. Furthermore, it has been shown that the treatment of OSA mitigates some of its negative consequences [13,16,[19][20][21], suggesting that, with readily available treatment options, OSA is a promising target to delay the onset of neurodegenerative disorders such as dementia, Alzheimer's disease (AD), or Parkinson's disease (PD).…”
Section: Introductionmentioning
confidence: 99%
“…While it is possible that some of these inconsistencies may at least, in part, be attributable to the small sample sizes or methodological differences such as different OSA definitions, age ranges, or uncontrolled confounders, these results might not be as contradictory as such. Rodents exposed to intermittent hypoxia have been shown to have increased brain water content, while sleep fragmentation and breathing pattern changes associated with obstructions have been shown to be independently associated with blood pressure fluctuations in humans, and increased GM was found to be co-localised with greater amyloid burden [11,21]. Furthermore, a recent study performed by Baril et al (2020) (N = 65) found that mild OSA was associated with widespread areas of lower diffusivity along the skeleton in the centre of white matter (WM) in projection, association, and commissural fibres but not the brainstem, as well as lower free-water fraction and no changes in fractional anisotropy (FA) or WM hyperintensity volume, while subjects with moderate to severe OSA showed lower axonal diffusivity in the corpus callosum (CC) [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notre objectif principal a donc été de préciser les atteintes cérébrales structurales, fonctionnelles et moléculaires associées à la présence d'apnées obstructives du sommeil chez des personnes âgées de plus de 65 ans, en utilisant une approche de neuroimagerie multimodale. Les résultats de cette étude ont été publiés dans la revue JAMA Neurology en mars 2020 [6]. Nous avons inclus 127 participants issus de l'essai clinique randomisé Age-Well [7] (https://silversantestudy.fr).…”
unclassified